Seminal Attributes, Freezability and their Interrelationships in Zebu Cattle and Buffalo Bulls from Central Gujarat - Pathak, PK; Dhami, AJ; Chaudhari, DV (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
A study was carried out on nine healthy mature breeding bulls (3 each of Gir, Surti and Murrah breed) to evaluate their fresh and frozen semen quality and their interrelationships. The ejaculates immediately after collection were evaluated for routine physicomorphological attributes, including HOS test. The ejaculates (n=72) having >75% initial motility were diluted @ 80 million sperm/ml using TFYG extender and the French mini straws filled were frozen in liquid nitrogen vapour using a programmable biofreezer. Thawing of straws was done at 37°C for 30 sec and assessed for freezability by conventional technique. All the cattle and buffalo bulls donated consistently normal thick creamy yellow and thick milky white semen, respectively. In Gir, Suti and Murrah bulls (n=24 ejaculate each) the seminal attributes such as ejaculate volume (6.69±0.17, 3.12±0.10 and 3.96±0.16 ml, p<0.01); initial motility (80.21±0.88, 84.58±0.60 and 84.38±0.76 %, p<0.01); total sperm output/ejaculate (9013.85±265.32, 3935.49±259.63 and 5366.48±332.99 million, p<0.01) and live sperm (84.71±0.83, 86.17±0.78 and 86.79±0.79 %, p<0.05) differed significantly. The mean percentages of post-thaw motile sperm (53.29±1.56, 58.33±1.43 and 59.58±1.20, p<0.01); live sperm (59.00±1.95, 67.00±1.59 and 68.42±1.66 %, p<0.01); and HOS reactive sperm (48.25±0.78, 44.21±1.29 and 51.54±1.29 %, p<0.01) in Gir, Surti and Murrah bulls semen also differed significantly. The variation among the bulls was significant for buffalo breeds in most of their fresh seminal attributes, except HOST, and for post-thaw motility, but not among Gir bulls. The important seminal attributes like motility, live sperm and HOS reactive sperm of fresh and frozen-thawed semen were significantly and positively interrelated in all three breeds of bulls (r = 0.40 to 0.81, p<0.05 to 0.01), suggesting that motility and HOST of fresh semen were good predictors of freezability of bovine semen